Changes in analgesic prescriptions in Dutch general practice - D. Veldkamp; N. Pooters; H. J. Schers; R. Akkermans; T. C. Olde Hartman; A. A. Uijen (Taylor & Francis Group, 2024)
Background Increases in opioid prescriptions have been described; however, recent trends and prescribing patterns of analgesics in Dutch general practice are largely unknown.Objective To investigate recent changes in the number of analgesic prescriptions, and the indications for prescribing strong opioids. Furthermore, we aim to identify risk factors for chronic opioid use in Dutch general practice.Design and setting A retrospective cohort study from 1 July 2013 to 31 June 2022, using a primary care practice based research network.Subjects Patients with ≥1 prescription for analgesics during the study period were included.Main outcome measure Changes in the number of prescriptions for paracetamol, non-steroidal anti-inflammatory drugs (NSAIDs) and opioids in Dutch general practice during the 9-year study period. Moreover, we analyzed indications for prescribing strong opioids by the general practitioner (GP).Results A total of 18,433 analgesic users were identified. Over time, prescriptions for paracetamol, NSAIDs and weak opioids decreased, while the number of strong opioid prescriptions increased. General practitioners prescribed more strong opioids for non-malignant pain, whereas prescriptions for malignant pain remained stable over time. Risk factors for chronic opioid use (≥90 days) included older age, lower educational level, smoking status and having a history of a musculoskeletal or psychological disorder, a malignancy or sexual, physical or psychological abuse.Conclusions Considering the increase in strong opioid prescriptions for benign conditions, GPs need to be vigilant for patients who are at risk for chronic use. Regular monitoring and awareness for psychosocial factors in treatment of chronic pain may be key in preventing harms associated with persistent opioid use.